Servant leadership and its relationship to school climate from the perspective of general secondary education teachers (Journal of Hama University, 2024)
The aim of this research is to determine the degree of application of servant leadership and its relationship to the school climate in secondary schools from the point of view of teachers in Lattakia Governorate, and the effect of variables (gender, academic qualification, number of years of experience) on that. In order to achieve the objectives of the research, the descriptive approach was used by designing A questionnaire consisted of (35) statements distributed over six dimensions. The research sample included (433) male and female teachers in secondary schools in Latakia Governorate. The research reached the following results:The degree of application of the dimensions of servant leadership was in the following order (human relations, community service, humility, employee empowerment, altruism), all of which were moderate.The level of school climate in secondary schools from the point of view of teachers in Latakia Governorate was moderate.- There is a positive, statistically significant relationship between servant leadership and school climate in secondary schools from the point of view of teachers in Latakia Governorate.- There are no statistically significant differences between the scores of the research sample members’ responses regarding the degree of application of servant leadership in Lattakia Governorate according to the academic qualification variable.- There are no statistically significant differences between the scores of the research sample members’ responses regarding the degree of application of servant leadership in Lattakia Governorate according to the gender variable.- There are statistically significant differences between the scores of the responses of the research sample members regarding the degree of application of servant leadership in Latakia Governorate according to the variable number of years of experience, in favor of teachers with more than ten years of experience.- There are no statistically significant differences between the scores of the responses of the research sample members regarding the level of the organizational climate in Latakia Governorate according to the variables (gender, academic qualification, number of years of experience).
Keywords: servant leadership, school climate, secondary schools